The impact of vitamin D3 supplementation on the course of acute obstructive bronchitis in young children - Yu.K. Bolbot; K.K. Hodiatska (Zaslavsky O.Yu., 2019)
Background. Acute obstructive bronchitis (AOB) ranks second among the respiratory diseases in children. In recent years, the results of clinical studies demonstrate a correlation between the low level of vitamin D (VD) and the risk of recurrent respiratory infections in adults and children. At the same time, the impact of VD insufficiency/deficiency and timely compensation of these changes on the frequency and severity of broncho-obstructive syndrome (BOS) in young children remains poorly understood. Thus, the purpose of the research was to study the features of VD level in young children with recurrent BOS and the efficacy of vitamin D3 supplementation on incidence and severity of the disease. Materials and methods. We examined 120 children with acute obstructive bronchitis. Group I included 60 patients with episodic BOS (up to 3 episodes per year), group II consisted of 60 children with recurrent BOS (3 or more episodes per year). The control group represented 30 healthy children of the corresponding age. We evaluated the severity of BOS and determined the serum level of 25-hydroxyvitamin D (25(OH)D) using an electrochemiluminescence method. Subsequently, the group of children with recurrent BOS was divided into two subgroups: IIa subgroup included 30 children who received vitamin D3 1000 IU daily throughout the year, IIb included 30 patients who were not supplemented with VD. The effectiveness of vitamin D3 supplementation was determined by the changes in the blood level of 25(OH)D, frequency and severity of BOS episodes. We used non-parametric methods for statistical analysis of data. For all types of analysis, the critical value of the significance level (p) was taken to be < 0.05. Results. The analysis of the clinical features of BOS episode showed that in the group of children with recurrent BOS compared to patients with episodic BOS the disease was characterized by a more severe course (23.3 % vs. 10.0 %, respectively; p = 0.034). We found that the mean VD level in children with recurrent BOS was 13.68 (7.96; 19.51) ng/ml and in children with episodic BOS 33.0 (28.19, 41.97) ng/ml (p < 0.001). The VD supplementation in the group with recurrent BOS was significantly lower than in children who were ill episodically (5 % vs. 60 %; p < 0.001). We showed that the risk of severe episode (OR = 3.06; 95% CI: 1.19-7.84; p = 0.019) and recurrent BOS (OR = 4.35; 95% CI: 2.75-6.86; p < 0.001) is higher in case of 25(OH)D level in serum less than 20 ng/ml. According to our data, VD supplementation in children for one year improves VD level (25.11 (12.14, 42.47) ng/ml vs. 14.48 (10.58, 23.47) ng/ml; p = 0.012) and reduces frequency of BOS episodes (1.0 (0.0; 2.0) in IIa subgroup vs. 2.0 (1.0; 3.0) in IIb subgroup; p < 0.001). On the background of vitamin D3 intake the severe course of BOS was not noticed, unlike the patients who did not receive it (0 % vs. 20 %, respectively; p = 0.031). Conclusions. VD deficiency occurs in 75 % of children with recurrent BOS. Moreover, the serum level of 25(OH)D below 20 ng/ml is associated with an increased risk of recurrent and severe episodes of BOS. Thus, supplementation with vitamin D3 1000 IU per day helps to increase the content of 25(OH)D in serum, to reduce the frequency and severity of BOS.